Evaluating The Quality of Teacher’s Talk in English Classroom Interaction at SMPIT Cahaya Bangsa Semarang - Alfat Prastowo; Sri Wuli Fritrianti; Widhiyanto Widhiyanto (English Education Journal, 2023)
Teachers talk play an essential role in classroom interaction, the study evaluated the quality of the teacher’s talk in English language class using Flanders (FIAC) system (1989) in Teacher‟s talk interaction. It aimed to evaluate seven of teacher talk quality in English classroom interaction. The study used a descriptive qualitative research design since involves human behavior in natural setting. The data was collected used audio recording and observed two class meetings at eighth grade of SMPIT Cahaya Bangsa Semarang which took approximately 160 minutes. One of English teacher was the subject and 29 students was the object in this study. The result of the study showed that asked questions was the most frequently shown which is 63 times, with percentage 36,2%. Giving direction was the often shown which is 47 times, with percentage 27,01%. Praises and encourages was the quite often shown which is 29 times, with percentage 16,66%. Lecturing was the quite rare shown which is 14 times, with percentage 8,04%. Accept feeling was the rarely shown which is 8 times, with percentage 4,6%. Criticizing or justifying authority was the rarely shown which is 7 times, with percentage 4,02%. Accepts and uses idea of students was the rarest shown which is 6 times, with percentage 3,44%. The evaluated of teacher‟s talk interaction quality that teacher focus on two interactions are asked questions and giving direction.